15 minus 6 divided by 2 is equal to 12.
The answer is -4.Since 8 divided by 4 is 2 and 2 minus 6 equals -4.
17
- 6 - 3 - 4 ÷ - 8 x 2 = -8
x = 1 1/2 = [14 dividedby (6x - 2) ] - [6 dividedby (3x - 1) ]
4
6 divided by 11 minus 1 divided by 2 equals?
-3
(x - 3x - 6) / 6 = (3x + 2) / 2 ∴2(3x + 2) = 6(3x + 2) ∴6x + 4 = 18x = 12 ∴12x = -8 ∴x = -2/3
-3
2 + (2/6) - 4 = -1.6 recurring (that is, -1.66666...)
6+9/5-2*6 = -4.2
6-3+8/2=5.5
2.5
2
6 / 3 - 4 * 6 = 2 - 4*6 = 2 - 24 = -22
30/2 = 15 x 7 = 105 - 6 = 99